Quizizz as a Digital Innovation in Arabic Vocabulary Learning: Teachers’ and Students’ Perspectives - Dadan Nugraha; Ghilatus Syabiha; Muhammad Fauzan Setiawan; Muhammad Ibnu Mutsni Andalusi (UIN Sunan Gunung Djati Bandung, 2026)
This study aims to provide an in-depth description of the Arabic language learning process at the Islamic Senior High School (MA) level by examining teachers’ instructional strategies, the use of learning materials, communicative approaches, and challenges that arise within a multilingual classroom context. The study also seeks to identify the effectiveness of the methods employed by teachers in developing students’ listening (istimā’), reading (qirā’ah), and speaking (kalām) skills, as well as to understand the supporting and inhibiting factors in the learning process, thereby serving as a foundation for developing more relevant pedagogical strategies. The research employs a qualitative method with a descriptive approach. Data were collected through classroom observations, in-depth interviews with Arabic language teachers, and document analyses of learning materials, lesson plans (RPP), and assessments used in MA. The analysis process included data reduction, data display, and conclusion drawing, while validity was ensured through source and technique triangulation. This method was chosen to obtain a comprehensive depiction of learning practices that naturally occur within the school context. The findings indicate that teachers employ a combination of interactive lectures, drills, question-and-answer sessions, and communicative approaches to enhance students’ language skills. The primary learning materials are sourced from the Ministry of Religious Affairs’ textbooks, yet teachers supplement them with audio media, vocabulary flashcards, and videos to strengthen comprehension. The main challenges include students’ varying levels of motivation, uneven foundational abilities, and limited instructional time. Nevertheless, adaptive strategies implemented by teachers, such as vocabulary reinforcement, gradual oral practice, and the use of contextualized examples, have proven effective in significantly improving students’ participation and understanding.